PELAKSANAANPEMBERIAN BANTUAN SOSIAL KEPADA MASYARAKAT YANG TERDAMPAK PANDEMI COVID-19 DI KOTA PEKANBARU - Rahmania, Yusi; Firdaus, Emilda; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Today's social assistance is one of the government's obligations to the underprivileged or the inability to maintain a maximum standard of living for those affected by the COVID-19 pandemic that is currently engulfing Indonesia. This is also in line with various regulations issued by the government during the COVID-19 pandemic. The purpose of writing this thesis: First, to find out the arrangements for providing social assistance to people affected by the COVID-19 pandemic in the city of Pekanbaru. Second, to find out the implementation and distribution of social assistance in the city of Pekanbaru.The type of research used in this legal research is sociological legal research. The research was conducted in the city of Pekanbaru. Analysis of the data used is the author analyzes the data qualitatively. In drawing conclusions, the writer uses deductive thinking method.From the research results, there are two main things that can be concluded. First, the regulation regarding the punishment of discriminatory health service actors is divided into five points, including: (1) Presidential Instruction Number 4 of 2020 concerning Refocussing Activities, Budget Reallocation and Procurement of Goods and Services in the Context of Accelerating Handling of Corona Virus Disease 2019 (Covid-19). , (2) Regulation of the Minister of Home Affairs Number 20 of 2020 concerning Handling Covid-19, (3) Regulation of the Minister of Home Affairs Number 39 of 2020 concerning Prioritizing the Use of Budget Allocations for Certain Activities, Allocation Changes, and Use of Regional Budgets, (4) Minister of Finance Regulation Number 254/PMK.05/2015 as amended by PMK Number 228/PMK.05/2016 concerning Social Assistance Expenditures at State Ministries/Institutions, Minister of Finance Regulation Number 43/PMK.05/2020 concerning Budget Execution Mechanisms State in Handling the Covid-19 Pandemic, (5) Riau Governor Regulation Number 29 of 2020 concerning Guidelines for Financial Aid Special Charity to Regencies or Cities to Improve the Quality of Social Safety Nets in handling the Impact of Covid-19 Sourced from the Riau Province Regional Revenue and Expenditure Budget for Fiscal Year 2020. Keywords: Covid-19 – Social Assistance – Social Welfare